Improving Grade V Learning Outcomes Through Project Based Learning Model at SD Negeri 3 Krajan - Rahayu, Denta Fitriana (Universitas Sebelas Maret, 2022)
This aim is to improve student learning outcomes in mathematics subjects in grade V elementary schools with the Project Based Learning (PjBL) learning model. The research carried out was classroom Action Research (PTK) with the stages being planning, implementation, observation, reflection. At each meeting a pretest and posttest are carried out to determine the progress of student learning outcomes. Student learning outcomes show that the Project Based Learning (PjBL) learning model can improve student learning outcomes, especially in Class V Mathematics at SD Negeri 3 Krajan.